Utilizing APIK Interactive Learning Media to Improve Literature Through Presenting Response Text - Faiqotur Rosidah; Dian Uswatun Hasanah (SEAMEO QITEP in Language, 2022)
Reading and writing are basic literacy that still needs to be cultivated, including for students. One of the literacy strategies is through learning. This research is Classroom Action Research (CAR) which aims to improve literacy in responding to texts through the use of APIK interactive learning media. The CAR in this study employed the model of Kemmis and Mc Taggart (1992). This research was conducted in two cycles, with each cycle consisting of planning, action, observation and evaluation/reflection stages. Each cycle was carried out for six meetings. Data collection was carried out using student activity observation sheets and learning outcomes tests which were analyzed quantitatively and qualitatively with descriptive analysis. In its application, it uses APIK syntax: (1) A, apperception or giving stimulation, (2) P, Pahami, students conduct surveys and listen to media, (3) I, implement, students compose response texts (4) K, communicate, students present their work. The subjects of this study were students of SMP Negeri 3 Peterongan, class 9H, for the academic year 2022/2023, as many as 27 students. The instruments used are observation sheets, documentation sheets, and the students’ writing in response texts. In the first cycle, the group’s results were 100% complete, individually 70% completed. As for the second cycle, the group completed 100% and individually 93%. Thus, there is an increase in student learning outcomes in the form of responding to texts. It can be concluded that APIK interactive learning media can improve students’ literacy through responding to texts.